Characterization of emerging and potentially emerging RNA viruses from sylvatic, rural, and urban environments in Colombia (2023)
ABSTRCT: The thesis objective allowed identify and characterize emerging and potentially emerging RNA viruses in sylvatic, rural and urban environments in Colombia. Chapter 1 presents the regional and temporal distribution of arboviruses of public health concern. The biological traits of arboviruses and their inherent capacity to infect various host and vector species, and the metagenomic next generation sequencing (mNGS) approach have proven to be reliable for discovery and monitoring of arboviruses in a variety of biological samples and different ecological scenarios. Chapter 2 describes the characterization of a wide variety of viruses in mosquitoes from the Sierra Nevada de Santa Marta in Colombia and along a sylvatic-to-rural-to-urban gradient, applying a mNGS approach, as well as other underlying evolutionary mechanisms that may partially explain the virus dynamics in this environment. Chapter 3 describes a new virus putatively named Guachaca virus (GUAV) that was identified from a Culex pipiens/Culex quinquefasciatus pool of mosquitoes collected in the rural area of Santa Marta, Colombia. The molecular characterization comprised viral isolation, NGS, 5'/3' RACE PCR, transmission electron microscopy, and phenotypic characterization in insect and vertebrate cells. Chapter 4 describes the origins of SARS-CoV-2 in Colombia and the routes of introduction into the country. The lineage diversity was confirmed by phylogenetic analysis and epidemiological transmission chains. Chapter 5 describes a novel, highly divergent lineage of SARS-CoV-2 with 21 exclusive mutations (10 nonsynonymous, 8 synonymous, and 3 located in non-coding regions). The amino acid alterations L249S and E484K found at the CTD and RBD of the Spike protein were shown to be of particular relevance. Chapter 6 describes the first report of the B.1.621 lineage of SARS-CoV-2, subsequently ratified by WHO as the Mu variant of interest with multiple amino acid changes in the Spike protein and wide dispersion in Colombia and several other countries. Chapter 7 presents the design and evaluation of a control RNA for real-time RT-PCR YFV detection and an approximation for YFV molecular test validation on clinical, entomological, and epizootic samples. Finally, the chapter 8 presents the general discussion, conclusions, perspectives and originality of the thesis.